1988
DOI: 10.1152/jappl.1988.64.2.803
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory, cardiovascular, and muscular factors related to exercise after precooling

Abstract: The effect of slightly lowered body temperature on endurance time and possibly related physiological factors was studied in seven male volunteers exercising on a cycle ergometer at an ambient temperature (Ta) of 18 degrees C. Work load was increased to 40% in a stepwise manner (phase I, min 0-16) followed by a period at 80% of peak oxygen consumption (VO2) sustained to exhaustion. On one day, exercise was preceded by a double cold exposure (precooling test, PRET), resulting in a 204-kJ/m2 negative heat storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
91
3
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 0 publications
14
91
3
1
Order By: Relevance
“…Cold exposure induced a lower initial T c and lower T c throughout exercise, and as a result heat storage was greater (Lee & Haymes, 1995). Exposure to cooler air (0 °C) also increased the work rate and cycling time to exhaustion at a cooler ambient temperature (18 °C), and like the previous study this was accompanied with lower T c at the beginning and during exercise compared to that of the control group (Schmidt & Brück, 1981;Olschewski & Brück, 1988). Taken together, these studies indicate that precooling with various methods can improve exercise time to exhaustion, most likely through reduced initial body temperature.…”
Section: Precoolingsupporting
confidence: 62%
See 1 more Smart Citation
“…Cold exposure induced a lower initial T c and lower T c throughout exercise, and as a result heat storage was greater (Lee & Haymes, 1995). Exposure to cooler air (0 °C) also increased the work rate and cycling time to exhaustion at a cooler ambient temperature (18 °C), and like the previous study this was accompanied with lower T c at the beginning and during exercise compared to that of the control group (Schmidt & Brück, 1981;Olschewski & Brück, 1988). Taken together, these studies indicate that precooling with various methods can improve exercise time to exhaustion, most likely through reduced initial body temperature.…”
Section: Precoolingsupporting
confidence: 62%
“…The decrease in the initial T c after precooling may explain the mechanism underlying enhanced performance in hyperthermia, through widening the capacity for heat storage and, consequently, increasing the time to reach a critical T c (Marino, 2002). sk after precooling facilitates a greater thermal gradient between core and skin such that heat storage capacity is increased, thereby attenuating cardiovascular and thermoregulatory strain (Olschewski & Brück, 1988;Lee & Haymes, 1995;Booth et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21] Direct comparisons with the magnitude of ergogenic effect observed in previous studies are limited because authors of only 2 studies 3,4 used the same protocol as we did, and only Kay et al 4 used the same mode of exercise. Kay et al 4 observed a 6.0% (900 m) improvement in performance when using an identical exercise protocol after 60 minutes of coolwater immersion, and Booth et al 3 observed a 4.2% improvement in distance run in 30 minutes after 60 minutes of coolwater immersion.…”
Section: Precooling Effectmentioning
confidence: 84%
“…Numerous strategies have therefore been designed to reduce the detrimental effects of dehydration on thermoregulation during exercise including precooling, fluid ingestion and plasma volume expansion (Olschewski and Bruck 1988;Lee 9 and Haymes 1995; Galloway and Maughan 2000;Watt et al 2000). The increased body mass associated with Cr loading has been attributed to osmotic effects resulting in cell swelling and increased protein synthesis (Haussinger et al 1993).…”
Section: Cr Supplementation and Endurance (Aerobic) Exercise Performancementioning
confidence: 99%